2003
DOI: 10.1046/j.0016-8025.2003.01052.x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the role of light during desiccation of three angiosperm resurrection plants

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(83 citation statements)
references
References 47 publications
(96 reference statements)
6
76
0
1
Order By: Relevance
“…This agrees with the hypotheses presented by Farrant et al, (2003) who described, that chlorophyll maintenance under drought should be balanced by ROS scavenging mechanisms. Indeed, we found that both total chlorophyll and carotenoids decreased under drought stress conditions.…”
Section: Correlation Analysissupporting
confidence: 82%
See 1 more Smart Citation
“…This agrees with the hypotheses presented by Farrant et al, (2003) who described, that chlorophyll maintenance under drought should be balanced by ROS scavenging mechanisms. Indeed, we found that both total chlorophyll and carotenoids decreased under drought stress conditions.…”
Section: Correlation Analysissupporting
confidence: 82%
“…In thylakoids it happens due to over-reduction of both photosystems (PS), which are no longer able to accept excess of excitation energy from light-harvesting chlorophyll protein complexes (LHCP) (Demmig-Adams and Adams, 1992; Reddy et al, 2004;Schmid, 2008). Such electron surplus that can lead to ROS formation can be avoided: (i) by degrading chlorophyll to primarily avoid ROS formation as in poikilochlorophyllous plants (Maslova and Popova, 1993;Keiper et al, 1998;; (ii) by retaining chlorophyll as in homoiochlorophyllous plants and simultaneously triggering the anti-oxidative scavenging mechanisms listed above to avoid further cell structure damage (Farrant et al, 2003). Many reports emphasize the role of carotenoids (especially xanthophylls) in direct deactivation of ROS in homoiochlorophyllous plants (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the leaves fold upward to a position where the adaxial surfaces are appressed against the stem (Fig. 1) and the sclerenchymous leaf ribs (Grundell, 1933) move closer to one another, thereby closing the leaf face, which has been proposed to minimize the exposure of the desiccated leaf to light (Farrant et al, 2003). Electron microscopy of hydrated and desiccated leaves revealed further morphological changes that occurred upon desiccation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mean in each column followed by same letters are not significantly different at the P 0.05 by one-way ANOVA with Duncan's multiple range tests For the photosynthetic pigment contents changes were reported on other resurrection plants species following dehydration and rehydration cycle, Boea hygrometrica (Deng et al 2000), Craterostigma plantagineum (Scott 2000), Sporobulus stapfianus (Quartacci et al 1997), Boea hygroscopica (Navari-Izzo et al 1995), Xerophyta sp. (Sherwin and Farrant 1996;Farrant et al 2003;Perez et al 2011), Reaumuria soongorica (Xu et al 2008), H. rhodopensis (Nagy-Deri et al 2011).…”
Section: Photosynthetic Pigmentsmentioning
confidence: 99%